Two Peoples – Two Stories: Anti-Immigrant Attitudes in Post-Socialist Russia. (16th August 2017) - Gorodzeisky, Anastasia; Glikman, Anya
Abstract: This article investigates mechanisms underlying anti-immigrant sentiment in post-socialist Russia in particular, and in societies undergoing a search for new national identity borders in general. We argue that when the borders of national identity are drawn and redefined, the forces that drive anti-immigrant attitudes differ meaningfully for members of the ethnic majority group and for members of the minority population. Our empirical analysis utilizes data obtained from a representative sample of the Russian population by the European Social Survey (2006-2012). Descriptive data reveal that the level of anti-immigrant attitudes among ethnic Russians (the majority population) is higher than among non-ethnic Russians (ethnic minority group), reflecting the fact that the crisis of national identity in post-socialist Russia has undermined, primarily, a sense of group position of ethnic majority. Our main findings demonstrate that in post-socialist Russia, as a society undergoing the critical period of the reconsideration of national identity, the anti-immigrant attitudes of the ethnic majority group rely mostly on perceptions of collective (state) vulnerability, while the anti-immigrant attitudes of ethnic minority groups rely to a greater degree on individuals' vulnerable socioeconomic position, and conservative views and ideologies (i.e., self-interests).